PERANG IDEOLOGI: MELACAK AKAR KONFLIK DUNIA - Yulian Rama Pri Handiki; Heni Indrayani (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2018)
War is a part of human civilization that is inevitable. It is used as an instrument to achieve certain political goals that have no connection with the war itself. The thing that is most often the center of attention in war is the physical form of war, but the most important thing that is often overlooked from war is the ideological discourse behind the war. In many wars in the world, ideological backgrounds were the main reason for war actors. Descriptive analysis of this shows that the real war in the world is ideological warfare.